(untitled) (Journal of Universal Excellence, 2026)
Research question (RQ): Do national screening programs reduce cancer morbidity and mortality? Purpose: The aim of the study was to conduct a systematic review of sources on three organized national screening programs and their impact on early detection and reduction of cancer. Methods: In the study, we used a descriptive method to review the literature and credible Internet sources on cancer related to the implementation of national screening programs. We excluded all popular and unprofessional sources and literature that was not freely available throughout the text. Results: Many cancerous and precancerous changes are successfully detected by national screening programs. Many diseases/changes detected at an early stage can be cured without invasive oncological treatment and late health consequences. Organization: Good organization of screening programs is essential for their effective implementation. Society: Adequate public awareness of the importance of taking care of one’s health is important to reduce overall morbidity in the population. Originality: We present not only the impact of screening programs on early cancer detection, but also important barriers that limit their full effectiveness in practice. Limitations/further research: The study examined the impact of three national programs on cancer incidence. For an overall assessment of program effectiveness and quality, we recommend conducting an in-depth survey involving program health care providers and assessing patient satisfaction.